TAXATION AS AN ALTERNATIVE TO ENCOURAGE IDLE LAND DEVELOPMENT - Abd Hamid, Muhamad Norfiqiri; Md Yunus, Norhidayah; Berahim, Nur; Zainudin, Ainur Zaireen; Mohd Ali, Hishamuddin; Najib, Muhammad; Razali, Mohamed; Mohd Yusoff, Nurul Syakima; Md Azmi, Fatin Afiqah (PLANNING MALAYSIA, 2023)
The topic of idle land, especially in agriculture, seems to have a consequence on both agricultural production and land utilization. Malaysia's government normally takes a diplomatic approach to idle land concerns, providing financial assistance, facilities, and agricultural input to urge landowners to develop the idle lands. Actual studies on the global scale, however, indicated that certain countries took a tough stance by implementing the idle land tax. Hence, the aim of the research is to look into nine countries' idle land taxation implementation. Secondary data were analysed using comparative and thematic analysis to examine the key aspects of idle land tax application. The study identified five fundamental aspects that are critical to the application of idle land taxes. Based on these findings, Malaysia now has new options for idle land enforcement that it may adopt in the future if diplomatic strategies no longer have an influence on Malaysia's approaches to overcome idle agriculture land issues.